Analisis Stabilitas Keuangan dan Tekanan Eksternal Terhadap Kecurangan Laporan Keuangan dengan Pendekatan Teori Keagenan - Vista Yulianti; Dian Sulistyorini Wulandari; Siti Sopiah (Journal of Trends Economics and Accounting Research, 2023)
The purpose of this study was to analyze the effect of Financial Stability and External Pressure on Financial Statement Fraud. The independent variables used in this study are Financial Stability and External Pressure, while the dependent variable is Financial Statement Fraud. This study uses secondary data. The population in this study are manufacturing companies in the food and beverage sector listed on the Indonesian stock exchange for the 2019-2021 period, totaling 26 companies. Determination of the research sample using purposive sampling technique in order to obtain a sample of 18 companies that meet the requirements. The data analysis method used is the classical assumption test, multiple linear regression analysis, and hypothesis testing. Based on the results of the study, it shows that the Financial Stability and External Pressure variables partially have no effect on fraudulent financial reporting and Simultaneously Financial Stability and External Pressure have no effect on fraudulent financial reporting.